Addition of Chaetomorpha sp Extract on the Growth and Hematology of Tilapia (Oreochromis niloticus) - Wahyuni, Sri; Nufus, Hayatun; Mursawal, Asri; Kurniawan, Ronal (Jurnal Natur Indonesia, 2024)
The use of phytoimmunostimulants from Chaetomorpha sp which is environmentally friendly and cost-effective. Apart from that, secondary metabolite compounds found in Chaetomorpha sp can improve the immune system. So, it can increase the fish's resistance to disease attacks, improve the digestive system, increase the fish's appetite, and save on feed use. This can be seen from hematological and physiological parameters. Therefore, researchers are interested in researching the effectiveness of the macroalgae Chaetomorpha sp as a phytoimmunostimulant. This research aims to look at the growth of tilapia and the immune system, which includes hematology and physiology of fish fed with warm water extract of Chaetomorpha sp for 30 days of maintenance. Data analysis used One-way ANOVA, and homogeneity was seen. If the analysis results show an effect, it is tested further using Student Newman Keuls (SNK). The research results show that adding Chaetomorpha sp extract influences the growth rate and survival of tilapia fish that are kept for 30 days. This maintenance shows that the administration of Chaetomorpha sp extract with a dose of 50mL/kg feed (T2) gave the best results on growth rate, feed efficiency, hematology, and tilapia survival, namely absolute weight 18.30g, LPS 5.38%/day, absolute length 3.98 cm, FCR 1.44, feed efficiency 69.18%, total erythrocytes 1.85x106 cells/mm3, hemoglobin 6.67 g/dL, hematocrit 35.33-37.67%, total leukocytes 2.42x104 cells/mm3, leukocrit 2.67%, blood glucose 43% and survival 93.33%.